2009
DOI: 10.1152/ajpheart.00292.2009
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial TLR4 is a determinant of neutrophil infiltration after global myocardial ischemia: mediating KC and MCP-1 expression induced by extracellular HSC70

Abstract: Cardiac surgery with global myocardial ischemia-reperfusion (I/R) induces a myocardial inflammatory response that impairs cardiac recovery. Chemokines contribute to the overall myocardial inflammatory response through inducing leukocyte infiltration. Although Toll-like receptor 4 (TLR4) has an important role in postischemic myocardial injury, the relative roles of myocardial tissue and leukocyte TLR4 in leukocyte infiltration, as well as the role of TLR4 in myocardial chemokine expression, are unclear. Our rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 35 publications
1
52
0
1
Order By: Relevance
“…In isolated perfused mouse heart subjected to global ischaemia and reperfusion, Ao et al . infused TLR4‐competent or TLR4‐defective neutrophils into TLR4‐competent or TLR4‐defective hearts during reperfusion, and observed that myocardial TLR4, rather than neutrophil TLR4, is the determinant of neutrophil infiltration after ischaemia 34. By using chimeric mice, Fallach et al .…”
Section: Discussionmentioning
confidence: 99%
“…In isolated perfused mouse heart subjected to global ischaemia and reperfusion, Ao et al . infused TLR4‐competent or TLR4‐defective neutrophils into TLR4‐competent or TLR4‐defective hearts during reperfusion, and observed that myocardial TLR4, rather than neutrophil TLR4, is the determinant of neutrophil infiltration after ischaemia 34. By using chimeric mice, Fallach et al .…”
Section: Discussionmentioning
confidence: 99%
“…Immunofluorescent Staining-Immunofluorescent staining was performed as described previously to co-localize oxLDL and TLRs following oxLDL stimulation (19). Briefly, cells were cultured in chamber slides to 30 -50% confluence.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, HSP72 is clearly the major component of the secreted eHSP70 found in the circulation, although recent evidence suggests that other forms may also be released into the blood, as recently pointed out by De Maio (2011). eHSP70 has been shown to bind to type 2 and 4 tolllike receptors (TLR2 and TLR4) on the surface of antigen-presenting cells (APCs) similarly to lipopolysaccharides (LPS), inducing the production of the pro-inflammatory cytokines IL-1 and TNF-, as well as NO (a product with prominent anti-microbial activity), in an NF-B-dependent fashion (Ao et al, 2009;Asea, 2003;Asea, 2008). Taken together, the above findings suggest that the body must attain a precise equilibrium between pro-inflammatory eHSP70 and anti-inflammatory intracellular HSP70 production in order to avoid chronic non-resolved inflammations, such as those observed in sepsis and during the onset of type 1 diabetes.…”
Section: Extracellular Hsp70mentioning
confidence: 89%